Public images of Mexico in South Korea (2020)
Public image analysis involves the process of managing a country’s image internationally. Such examination is particularly important to gain an understanding of a policy’s effectiveness in the target country and to reflect S-F / Shutterstock.com 39 MAP | REVISTA MUNDO ASIA PACÍFICO | Vol. 9, No. 17 upon its undesired signals to design positioning strategies in a partner country’s society. Therefore, public opinion surveys are the key to achieving specific desired aims in other societies. This research paper provides hard data to inquire about popular Korean perceptions of Mexico as the main pillar of the latter’s positioning in Asian society. Analysis of the responses reveals several enriching elements that are not highlighted by media images.